Developing public health capacities of Frontline Public Health Workforce in Uttarakhand - Singh, Pankaj; Gupta, Amrita; Tripathi, Akhilesh; Dhuria, Meera; Aggarwal, Pradeep (Indian Journal of Community Health, 2022)
Recent COVID-19 pandemic has highlighted the importance of increase in the ability of public health workforce to detect and respond to the public health threats. For timely implementation of an adequate response and mitigation measure, the standardized and sustainable capacity building programme for frontline public health workforce is the need of hour. National Center for Disease Control (NCDC), Ministry of Health and Family Welfare, in partnership with U.S. Centers for Disease Control and Prevention (CDC), developed a three-month in-service Basic Epidemiology Training programme. This is a tailor-made programme for frontline public health workforce to strengthen epidemiological skills. This training was a practical interactive approach to field epidemiology for three months on the job training for frontline public health workforce that addressed the critical skills needed to conduct surveillance effectively at the local level while focusing on improving disease detection, reporting and feedback. The training also demonstrated the role of learning model in form of interaction between the mentor and the mentees. The importance of handhold support given by the mentors to the mentees in quality outbreak investigations and documentation.